Papers on differential equations in the Memoirs of the Natural Science Society in Paris - Koroński, Jan (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2013)
This paper concerns the general characteristics of the Natural Science Society in Paris and the Memoirs of the Natural Science Society in Paris. Moreover, in the context of the development of the theory of differential equations in the world, we present in this paper the articles of Y. Villarceau (1813), W. Zajączkowski (1837–1898) and W. Folkierski (1842–1904) on differential equations, which were published in Memoirs of the Natural Science Society in Paris.